STUDIES ON THE EFFECT OF NERIUM FLOWER PRESENCE ON THE POST-EMBRYONIC DEVELOPMENTAL SCHEDULE AND REPRODUCTIVE POTENTIAL OF EARIAS VITTELLA (F.) (LEPIDOPTERA : NOCTUIDAE) - DASS, IVAN J; KRISHNA, S. S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1989)
Presence of nerium flower (Thevetia peruviana (Pers.)) in the rearing environment of the spotted bollworm, Earias vitrella (F.) brought an overall improvement in the rate of larval development and in the numerical strength of the adults that finally emerged. The reproductive potential of the moths, in terms of egg output and egg hatchability, also significantly shot up when the insects interacted with this flower all through right from the first day of their larval life. However, such a stimulative role of nerium flower in the regulation of reproduction of this noctuid species became only an adjunct to a similar part played by sucrose nutrition acquired by the adults.